2010
DOI: 10.23917/forgeo.v24i2.5021
|View full text |Cite
|
Sign up to set email alerts
|

Tinjauan Kerentanan, Risiko dan Zonasi Rawan Bahaya Rockfall di Kulonprogo, Yogyakarta

Abstract: This research aims at identification of spatial plan zonation in rockfall prone areas. Research method applies hazard, vulnerability and risk analysis as an input for spatial modeling using Multi Criteria Evaluation (MCE). Research reveals that in Girimulyo is Kerentanan, risiko, rockfall, zonasi, evaluasi multi kriteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The rockfall hazard has the potential to inflict dangerous and severe impacts on human life (van Westen and Greiving 2017), but the risks and hazards of rockfall are varying based on the conditions of the area (Ansari et al 2016;Budetta 2004). The natural and physical characteristics of the hilly area were suspected to be the cause of rockfall events, and the hazard level will be higher if the area were experiencing hills excavation for transportation facilities (Hizbaron et al 2010). Along the roads produced from excavated hills, rockfall is definitely to be one of the most potential threats that could happen, but not all segments of the roads have the same levels of hazard.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rockfall hazard has the potential to inflict dangerous and severe impacts on human life (van Westen and Greiving 2017), but the risks and hazards of rockfall are varying based on the conditions of the area (Ansari et al 2016;Budetta 2004). The natural and physical characteristics of the hilly area were suspected to be the cause of rockfall events, and the hazard level will be higher if the area were experiencing hills excavation for transportation facilities (Hizbaron et al 2010). Along the roads produced from excavated hills, rockfall is definitely to be one of the most potential threats that could happen, but not all segments of the roads have the same levels of hazard.…”
Section: Introductionmentioning
confidence: 99%
“…The rockfall incidents have occurred several times in Yogyakarta. Hizbaron et al (2010) have identified 16 rockfall events that occurred in 1970-2009 in Yogyakarta and discovered that the high vulnerability area of rockfall was located along the transportation route. Afterward, a rockfall incident occurred in 2011 on Yogyakarta Southern Mountain hills that fell into settlements and caused casualties (Mustopo 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The rockfall hazard has the potential to inflict bad and severe impacts on human life (van Westen & Greiving, 2017), but the risks and hazards of rockfall are varying based on the conditions of the area (Ansari et al, 2016;Budetta, 2004). The natural and physical characteristics of the hilly areas were suspected to be the cause of rockfall events and the hazard level will be higher if the area experiencing hills excavation for transportation facilities (Hizbaron et al, 2010). Along the roads produced from excavated hills, rockfall is certainly to be one of the most potential threats that could happen, but not all segments of the roads have the same levels of hazard.…”
Section: Introductionmentioning
confidence: 99%
“…The rockfall incidents have occurred several times in Yogyakarta. Hizbaron et al (2010) in his research have identified 16 rockfall events that occurred in 1970-2009 in Yogyakarta.…”
Section: Introductionmentioning
confidence: 99%